The funding and the education: bibliometric study (2000-2021) - Beltrán Viedma, María José; Gallego Valero, Leticia (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
A bibliometric research is carried out on the scientific production in the Scopus database, for thr words “multilateral funding education”, delimiting the period between the years 2000-2021. The documents have been quantified and classified, analyzing the themes, the countries and institutions that have the greatest production and the most cited publications. The results allow us to verify a very important growth in production, especially from 2011. It is concluded that the research theme has not reached consolidation and is insufficient despite the constant rise in the period analyzed.